Impact of school day extension on educational outcomes: Evidence from Mais Educaç\~ao in Brazil - Luis Felipe Batista de Oliveira; Rafael Terra de Menezes (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
There are many elements to the public policies required to reduce educational disparities among students. They include issues related to infrastructure, remuneration and training of education professionals, and debates regarding unifying content at the national level and on forms of public service provision and delivery. There are also suggestions regarding how students can best make use of their time to seek to expand their knowledge, relationships and school participation. While there are many initiatives that focus on all of these aspects, their impacts are not always subject to a causal analysis capable of providing the information necessary to improve them. This Working Paper provides evidence regarding the impact of the extended school days implemented under the Programa Mais Educaç\~ao ('More Education' programme - PME), an initiative of the Brazilian federal government. The PME transfers funds directly to educational institutions, which, in turn, purchase educational materials and fund monitoring grants for extracurricular activities. [...]
Keywords: 330; impact; school day extension; educational; outcomes; evidence; Mais Educaç\~ao